Genetic differentiation within and away from the chromosomal rearrangements characterising hybridising chromosomal races of the western house mouse (Mus musculus domesticus) - Förster, Daniel W. (2016)
Fil: Förster, Daniel W. Universidad de York. Departamento de Biología; Reino Unido.